1975 : o dispositivo engajamento : Zero, de Ignácio de Loyola Brandão, e El otoño del patriarca, de Gabriel García Márquez - Ribeiro, Pedro Mandagará (2012)
This dissertation is part of a contemporary trend of writing the literary history of a single year in this case, 1975. To do that, I take Michel Foucault s concept of apparatus, and its development by Hans Ulrich Gumbrecht and Giorgio Agamben, and describe the apparatus of engagement. The apparatus is described genealogically, through readings of Jean-Paul Sartre and Theodor Adorno. I show that the concept of engagement has three different meanings, which I describe as three levels. The novels Zero, by Ignácio de Loyola Brandão, and El otoño del patriarca, by Gabriel García Márquez, both published in 1975, are analyzed in what pertains to their narrators and protagonists, and the results are compared to the described levels of engagement. The conclusion shows that there is a presence of the apparatus of engagement in these novels. In the concluding remarks, the historical inscription of the novels is discussed, both relating to Latin American general history and to cultural and literary history